2021
DOI: 10.1080/15548627.2021.1899667
|View full text |Cite
|
Sign up to set email alerts
|

TNF-induced necroptosis initiates early autophagy events via RIPK3-dependent AMPK activation, but inhibits late autophagy

Abstract: Stork (2021): TNF-induced necroptosis initiates early autophagy events via RIPK3-dependent AMPK activation, but inhibits late autophagy, Autophagy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 80 publications
(134 reference statements)
1
42
0
Order By: Relevance
“…Both Yersinia and Listeria have been shown to activate autophagic mechanisms, and it was suggested that those mechanisms facilitate the destruction of the bacteria [44,45]. Activation of MLKL was also reported to facilitate autophagy [46]. It, therefore, seems plausible that the lysosomal destruction of intracellular bacteria that we found to be induced by ubiquitinated MLKL is exerted via enhancement of autophagy.…”
Section: Mlkl Ubiquitination Also Facilitates the Destruction Of Some Other Intracellular Bacteriasupporting
confidence: 51%
“…Both Yersinia and Listeria have been shown to activate autophagic mechanisms, and it was suggested that those mechanisms facilitate the destruction of the bacteria [44,45]. Activation of MLKL was also reported to facilitate autophagy [46]. It, therefore, seems plausible that the lysosomal destruction of intracellular bacteria that we found to be induced by ubiquitinated MLKL is exerted via enhancement of autophagy.…”
Section: Mlkl Ubiquitination Also Facilitates the Destruction Of Some Other Intracellular Bacteriasupporting
confidence: 51%
“…RIPK3, a necroptosis-regulating kinase, has been found to be closely associated with lysosomal biogenesis ( 41 , 42 ). In TNF-treated murine L929 fibroblasts, RIPK3 promoted necroptosis by blocking lysosomal degradation of autophagosomes ( 43 ). In septic acute kidney injury, upregulated RIPK3 contributes to lysosomal dysfunction and the accumulation of autophagosomes in renal proximal tubular epithelial cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely to the well-regulated and cytoprotective mechanism of autophagy, necroptosis constitutes an inflammatory form of cell death, leading to tissue necrosis [ 98 , 99 ]. Necroptosis is mainly mediated by death receptors like TNFRSF1A/TNFR1 (TNF receptor superfamily member 1A), although there are other pathways leading to necroptosis as well [ 100 ].…”
Section: The Link Between Endoplasmic Reticulum (Er) Stress Oxidative...mentioning
confidence: 99%
“…Necroptosis as well as autophagy are mechanisms balancing cell death and survival, and a crosstalk between these two mechanisms has been reported [ 98 ]. Wu et al demonstrated the link between autophagy and necroptosis, since RIPK3 connects directly with AMPK, phosphorylating its catalytic subunit PRKAA1/2 at T183/T172.…”
Section: The Link Between Endoplasmic Reticulum (Er) Stress Oxidative...mentioning
confidence: 99%
See 1 more Smart Citation